Menggagas Pengaturan dan Penerapan Central Bank Digital Currency di Indonesia: Bingkai Ius Constituendum - Syafira Nurullia (Fakultas Hukum, Universitas Internasional Batam, 2021)
Bank Indonesia has the desire to create a digital representation of money which is a symbol of its country's sovereignty called the Central Bank Digital Currency (CBDC). However, CBDC also presents risks, especially in the legal aspects in Indonesia. The purpose of this paper is to complement the shortcomings of previous studies by carefully examining how ideally the governance and implementation of CBDC is in Indonesia, in the ius costituendum frame. The method used is normative juridical which is qualitative in nature based on library research. Data sources come from secondary data sources and tertiary data. The data were analyzed using a deductive mindset with descriptive and analytical methods. The results of the study are that the implementation of CBDC requires governance in the field of law, technology infrastructure readiness and community readiness as well as governance regarding the supervision and stability of CBDC values in Indonesi. An important conclusion from this study is the need for a legal product that regulates the implementation and protection of the community in the use of CDBC in Indonesia.